Analysis of the use of the ITIL methodology against other reference frameworks for service management 2018-2020 (LACCEI, 2024)
A systematic mapping of articles was carried out that propose a management model based on the ITIL methodology, used for the management of information technology services, focused as a basis on the difficulties that an organization may have when trying to implement in the best way and coping with difficulties such as financial, time, and resource constraints, lack of a strategic plan, lack of skills and staff skills. These difficulties must be solved to subsequently implement an adequate service model according to the organization, as are also the other frameworks, ISO / IEC 20000, COBIT or CMMI-SVC, which learned the service life cycle in order to provide a greater value to the business. In the development of this research, areas, interdisciplinary groups and tools are used that satisfy the problem of complex relationship between business and technology. For this reason, we classify the studies into three categories, which closely depend on the needs and solutions that organizations require regarding the implementation of ITIL. As a result, it was obtained that in three years there was an increase in the implementation of the ITIL framework, as well as the good Management of information technology services.